Public payment of accounting professionals in Colombia (2014)
The Public Accounts in Colombia, is a profession with a relevant importance in the national economy and in each of the companies to independent level; however there is widespread dissatisfaction with the professionals who practice in the value that has been given the part of society, and the low pay that is received for the provision of these services. It is the task of all: both professionals in public accounting and enterprises and the state, look for tools to reach a balance in which the practitioner is satisfied doing their work and ease with consideration and also the client not seen as an obligation, or a mere compliance with the requirement to purchase provided by the professional service.